Health Belief Model: Determinants of Hypertension Prevention Behavior in Adults at Community Health Center, Sukoharjo, Central Java - Ratna Setiyaningsih; Didik Tamtomo; Nunuk Suryani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: According the WHO the estimated of age standarized prevalence of High blood presure in adults age 25+ years in Indonesia in 2008 was 42.7% in men and 39.2% in women. Hypertension deaths in Indonesia reached 42.226 or 3.02% of total deaths in 2014. Age-adjusted death rate was 25.26 per 100.000 of population (ranked 29 in the world). The prevalence of hypertension in Sukoharjo, Central Java, was 36.827 cases in 2015. This study aimed to examine the determinants hypertension prevention behavior using Health Belief Model.Subjects and Method: This was an analytic and observational study with cross sectional design. This study was conducted in Sukoharjo, Central Java, Indonesia, from September to October 2016. A total of 160 patients visiting Sukoharjo Community Health Center, Sukoharjo, Central Java, was selected for this study by simple random sampling. The sample consisted of 83 (51.9%) patients aged <35 years and 77 (48.1%) patients aged ≥35 years. The exogenous variables were perceived vulnerability, perceived seriousness, cues to action, perceived benefits, perceived barrier, and self efficacy. The endogenous variables were perceived threat and hypertension prevention behavior. The data were collected by questionnaire and analyzed by path analysis.Results: The path model showed goodness of fit with indices as follows: CMIN= 9.03, p=0.172, GFI= 0.99, NFI= 0.99, CFI= 1.00, and RMSEA= 0.06. Self-efficacy (b= 0.11; p<0.001; β=0.31), perceived benefit (b=0.12; p=0.005), and perceived threat (b=-0.10; p<0.001), had positive and statistically significant effect on hypertension prevention behavior. Perceived barrier (b=-0.10; p<0.001) had negative and statistically significant effect on hypertension prevention behavior. Perceived vulnerability (b=0.35; p<0.001), perceived of seriousness (b=0.48; p<0.001), and cues to action (b=0.33; p<0.001) had indirect positive effects on hypertension prevention behavior.Conclusion: Self-efficacy, perceived benefit, and perceived threat, have positive effect on hypertension prevention behavior. Perceived barrier have negative effect on hypertension prevention behavior. Perceived vulnerability, perceived of seriousness, and cues to action have indirect positive effects on hypertension prevention behavior.Keyword: hypertension, prevention behavior, health belief model.Correspondence: Ratna Setyaningsih. School of Nursing Bhakti Mulia, Sukoharjo, Central Java. Email: ratnaa_ zeitiyanie@yahoo.co.id.Journal of Health Promotion and Behavior (2016),1(3): 161-171https://doi.org/10.26911/thejhpb.2016.01.03.03